Optimizing The Prototype Curriculum Based on Religious Values and Local Wisdom through The Principal's Role - Saidek, Abdul Rahim (JURNAL AL-TANZIM, 2023)
This article aims to analyze the role of the principal in optimizing a prototype curriculum based on religious values and local wisdom in one of the Aliyah Negeri Madrasahs in Jambi Province. This study seeks to reveal the phenomena and meanings in the field, so the researcher uses a qualitative phenomenological approach to answer this. Observation, interviews and documentation were carried out to collect data in the field. While the data analysis was carried out in stages, starting from data collection, reduction, data display, and conclusion. The results of the study show that the role of the madrasa head in optimizing the prototype curriculum based on religious values and local wisdom is shown through; the head of the madrasa as a pioneer of reform, analyzing the needs of curriculum prototypes, curriculum design based on religious values and local wisdom, skills improvement, continuous monitoring and evaluation. This research provides implications for the importance of innovation, renewal, sensitivity and leadership strategic steps in responding to societal demands and the challenges of the times.